2021
DOI: 10.1038/s41598-021-87846-z
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of antimicrobial prophylaxis at 30 versus 60 min before cesarean delivery

Abstract: This study aimed to examine the effect of antibiotic prophylaxis (AP) given within 30 compared to 30–60 min before skin incision on the incidence of infectious morbidity after cesarean delivery (CD). A retrospective cohort study was conducted at a single institution on data between 2014 and 2018. Women who delivered by CD were divided into two groups according to AP timing before skin incision: group 1 within 30 min, and group 2 from 30 to 60 min. The primary outcome was the incidence of any infectious morbidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Previous study reported that the rate of infectious morbidity was similar among women who received prophylactic antibiotics within 30 min and 30–60 min before skin incision. 32 Prophylactic antibiotics might be beneficial for women, but uncertainty regarding the consequences for the baby remains, which should be examined in future prospective research studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study reported that the rate of infectious morbidity was similar among women who received prophylactic antibiotics within 30 min and 30–60 min before skin incision. 32 Prophylactic antibiotics might be beneficial for women, but uncertainty regarding the consequences for the baby remains, which should be examined in future prospective research studies.…”
Section: Discussionmentioning
confidence: 99%